Tindakan Kedokteran Tanpa Persetujuan Tertulis Pasien pada Klinik Pratama Kecantikan Estetika - Pramudita, Maya (Universitas Ekasakti, 2023)
This study aims to analyze the responsibility of doctors who carry out medical procedures without written consent for patients at the Pratama Aesthetic Beauty Clinic and also to analyze the legal protection for patients who do not provide written consent for medical procedures at the Aesthetic Beauty Pratama Clinic. Administratively, it is the responsibility of a doctor to carry out medical procedures without written consent from the patient administratively. The legal responsibility of doctors, apart from civil law, is also accountable under criminal law. In Indonesia, the problem of liability for a doctor's criminal law is regulated in the Criminal Code, which includes legal responsibility arising on purpose or negligence/negligence. Forms of legal protection for patients for medical record errors resulting from the absence of informed consent in health services are regulated in Law Number 36 of 2009 concerning Health Law Number 29 of 2004 concerning Medical Practice and Law Number 8 of 1999 concerning Consumer Protection where these three rules can provide protection and legal certainty for patients who also serve as consumers about the rights and obligations of patients in obtaining health services which in practice are not by applicable laws.